EVOLUTION OF HAFIZABAD DISTRICT A CASE IN HISTORICAL GEOGRAPHY - Khan, Imran; ALI SHIRAZI, SAFDAR (International Journal of Psychosocial Rehabilitation, 2021)
The study of the evolution of Hafizabad in the context of historical geography is very important in the new trends of research. Taking these aspects of geography in mind to make research in the historical geography of Hafizabad has become a significant study that will evaluate the many diverse features of the district Hafizabad. This study will explain the evolution of Hafizabad District as it has historical and geographical importance and special reference to the political and historical changes in the Punjab and Indian subcontinent. Hafizabad remained an important area and administrative unit since the days of Mughal Emperor Akbar and played an important role, so the research work on the historical evolution of this district will be a unique work.